Revelation of the mediation role of moral sensitivity on safety attitude and personality traits among critical care nurses - Hind Ismail Ali; Ahmed Abdellah Othman; Mohamed Hussein Ramadan Atta; Sanaa Saber Mohamed; Seham Hassan Mohamed (BMC Nursing)
Abstract Background Critical care nurses face complex ethical dilemmas and high-pressure situations that require quick ethical decision-making. Personality traits have been recognized as influencing individuals’ ethical decision-making processes and attitudes toward safety in healthcare. Moral sensitivity helps nurses recognize ethical issues and respond appropriately to these challenges. So, this study aimed to assess the mediation role of moral sensitivity on safety attitudes and personality traits among critical care nurses. Method This study used a convenience sample method and a descriptive correlational research design to conduct it on 232 critical care nurses who worked at intensive care units and emergency departments of nine Sohag Governmental Hospitals. Three tools were used to collect data: the Moral Sensitivity Questionnaire (MSQ), the Big Five Factors of Personality Inventory sheet, and the Safety Attitudes Questionnaire (SAQ). The data were analyzed using descriptive statistics and inferential tests (multivariate linear regression using the backward method). Result The study revealed the personality profiles of the participants, with a total personality traits mean score (150.012 ± 9.628) and higher mean scores in conscientiousness and openness. The highest mean in moral sensitivity was interpersonal orientation, 22.76 ± 3.339, and moral meaning, 26.97 ± 4.279. Participants had low average mean scores regarding safety attitude 73.254 ± 11.368. There was a positive correlation between personality traits, moral sensitivity, and safety attitude. Finally, moral sensitivity acted as a mediating factor between personality traits and safety attitude. Conclusion The results of the present study suggest that personality assessment and moral sensitivity training be incorporated into nursing education and professional development programs. By enhancing nurses’ self-awareness and sensitivity to ethical dilemmas, institutions can potentially improve safety attitudes and, consequently, patient care outcomes.